The effect of metacognitive abilities on junior high school students in the Republic of Vanuatu when solving mathematical word problems - Sawah, Kency Obed; Kusaka, Satoshi (International Journal of Innovative Research and Scientific Studies, 2025)
Mathematics achievements in Vanuatu remain a major concern for mathematics education within the Vanuatu education system. The level of students’ ability to reflect on their thinking processes and choose an effective strategy to solve a problem is an indicator that requires immediate attention to exploring possible solutions. Along this line, this study was intended to investigate the use of metacognitive abilities and their effectiveness in solving mathematics word problems among Junior High School students in the Republic of Vanuatu. Metacognitive abilities, which are often described as “thinking about one’s thinking,” encompass two categories. The first is metacognitive knowledge, which refers to people, tasks, and strategies. The second is metacognitive skills, which comprise self-monitoring, self-evaluation, and self-control. The study compares the effectiveness of these metacognitive abilities among 39 grade eight students and 28 grade nine students of Kawenu Junior High School in Port Vila, Vanuatu. One non-routine word problem was used similarly in both grades. The problem-solving process involves quadratic equations. The responses from students were assessed from the six perspectives described above. The findings revealed 62% of correct responses in year eight, while 68% of correct responses were obtained in year nine. These results indicated that correct responders rely more on their cognitive strengths during problem-solving, likely drawing on prior knowledge or automaticity, while incorrect responders struggle to apply effective cognitive strategies, even when they engage in pre-solution metacognitive activities. Furthermore, according to the Grounded Theory Approach used for the analysis of this study, the examples of students’ responses observed demonstrated that when metacognition is used effectively, it helps students connect new problems to previously learned material, engage in self-reflection, and monitor their problem-solving strategies. On the other hand, when metacognition is either absent or improperly used, students struggle to articulate clear strategies or fail to connect their reasoning to underlying mathematical concepts.